2016
DOI: 10.5603/ep.2016.0012
|View full text |Cite
|
Sign up to set email alerts
|

Wydzielanie serotoniny i melatoniny u kobiet po menopauzie z zaburzeniami odżywiania

Abstract: Introduction: Postmenopausal women manifest emotional disorders associated with an increase in appetite. The aim of the study was to assess the serotonin and melatonin secretion and metabolism in postmenopausal women in relation to eating disorders. Material and methods: Sixty postmenopausal women and 30 women without hormonal disturbances were enrolled into the study and divided into three groups: group I (control) -women without menstrual disorders, group II -postmenopausal women without appetite disorders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
(31 reference statements)
0
8
1
2
Order By: Relevance
“…However, only a few studies have analyzed the relationship between serotonin and melatonin levels and the correlation with the blood serum. Modai et al [61] analyzed 10 healthy men, and Chojnacki et al [62] presented serotonin and melatonin secretion in postmenopausal women with eating disorders. To the best of our knowledge, only Rao et al [63] and Bozhko et al [64] provided an analysis of depressed patients after they had received light therapy.…”
Section: Circadian Rhythm and Melatonin In Depressionmentioning
confidence: 99%
“…However, only a few studies have analyzed the relationship between serotonin and melatonin levels and the correlation with the blood serum. Modai et al [61] analyzed 10 healthy men, and Chojnacki et al [62] presented serotonin and melatonin secretion in postmenopausal women with eating disorders. To the best of our knowledge, only Rao et al [63] and Bozhko et al [64] provided an analysis of depressed patients after they had received light therapy.…”
Section: Circadian Rhythm and Melatonin In Depressionmentioning
confidence: 99%
“…The reasons for these remains unclear but likely multifactorial. There are several prior findings probably relevant and worth discussing [34,35,36]. Melatonin, a hormone secreted by the pineal gland, has been found to be relevant to female hormone and obesity [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…There are several prior findings probably relevant and worth discussing [34,35,36]. Melatonin, a hormone secreted by the pineal gland, has been found to be relevant to female hormone and obesity [34,35]. Prior study reported that alterations in the metabolism or a disturbed circadian pattern of melatonin may play a role in the development of delirium [36].…”
Section: Discussionmentioning
confidence: 99%
“…Un creciente cuerpo de evidencia apoya el rol de las hormonas reproductivas, específicamente el estrógeno, para el riesgo de TCA y síntomas relacionados. Al igual que la pubertad, la peri-menopausia se caracteriza por cambios estrogénicos que conllevan una vulnerabilidad para el desarrollo o reaparición del TCA 3,32 .…”
Section: Etiopatogenia/comorbilidadunclassified
“…caquexia, neumonía o insuficiencia cardíaca). Aproximadamente, 42% se benefició del tratamiento, siendo el enfoque más exitoso la terapia combinada (psicoterapia cognitivo-conductual y medicamentos) 50 y eventualmente de remplazo hormonal en mujeres posmenopáusicas 32 . Forman y Davis 51 observaron que al ingreso hospitalario por un TCA, las pacientes de mediana edad experimentaron un mayor cambio positivo con respecto a la depresión y a la insatisfacción con la imagen corporal y describieron la terapia familiar y grupal focalizada en la pérdida y el dolor como significativamente más útiles que en las pacientes adultas jóvenes.…”
Section: Tratamientounclassified